MUTASI STRUCTURAL INTRON trnL (UAA) PADA SUKU MERANTI-MERANTIAN (DIPTEROCARPACEAE) - Yulita, Kusumadewi Sri (BERITA BIOLOGI, 2007)
tRNA " UAA (trnL) intron have been widely utilised for phylogenetic reconstruction in angiosperm families. Two main helical elements of secondary structure of trnL intron (stem loop regions P6 and P8) contained the most variable sequences across taxa.Detailed examination on the insertion-deletion events in trnL intron sequences of 110 species of Dipterocarpaceae has identified 4 stem loop structures within both loops.The first stemJoqp was found in P6 loop and three other were discovered in P8 loop.These structures featuring characteristic for genericJinfra-generic level depended upon which taxonomic classifications are foJJowed.One of these structures formed a large loop of 72 nucleotides and was a unique major stem loop in Dipterocarps family whose loop was the major structural mutation of trnL intron in this family.